2020
DOI: 10.1007/s12011-020-02114-x
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Increases Iron Export by Modulating Ferroportin 1 Expression Through the Ghrelin/GHSR1α/MAPK Pathway in the Liver

Abstract: Background: The liver is the metabolic organ considered to contribute the most to maintaining body iron homeostasis and is a regulator of body adaptation to fasting. Our previous studies implied a negative relationship between iron and ghrelin in both mice and humans and indicated that ghrelin was able to increase ferroportin 1 (Fpn1) expression in the spleen and macrophages through the GHSR/MAPK pathway. However, it remains to be explored whether fasting or ghrelin has a functional effect on iron homeostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…Ghsr expression was not detectable in either controls or Kiss1-GHSR KO females (data not shown), these findings are corroborated in multiple publications [ 57 , 58 ]. More recent publications have found that liver Ghsr expression does increase to detectable values after a 24 h fast, which we did not do [ 59 , 60 ]. These findings indicate that the differences in glucose levels after a 5 h fast are due, in part, to the central deletion of GHSR from Kiss1 neurons and not a peripheral deletion.…”
Section: Resultscontrasting
confidence: 86%
“…Ghsr expression was not detectable in either controls or Kiss1-GHSR KO females (data not shown), these findings are corroborated in multiple publications [ 57 , 58 ]. More recent publications have found that liver Ghsr expression does increase to detectable values after a 24 h fast, which we did not do [ 59 , 60 ]. These findings indicate that the differences in glucose levels after a 5 h fast are due, in part, to the central deletion of GHSR from Kiss1 neurons and not a peripheral deletion.…”
Section: Resultscontrasting
confidence: 86%
“…Total RNA extraction and RT‒PCR analysis were performed essentially as described previously ( Luo et al, 2021 ). Primer sequences were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction and RT‒PCR analysis were performed essentially as described previously [21]. Primer sequences were as follows:…”
Section: Methodsmentioning
confidence: 99%